Does harvest residue management influence biomass and nutrient accumulation in understory vegetation of Eucalyptus globulus Labill. plantations in a Mediterranean environment ? - Carneiro, M. (2009)
The effect of harvest residue management options on biomass and nutrient accumulation in understory vegetation, as well as the contribution of understory to nutrient cycling, were assessed during the early rotation stage of a Eucalyptus globulus Labill. plantation in Central Portugal. The effects of residue management options on early tree growth were also evaluated. Treatments established at the time of plantation and replicated four times in a simple completely randomised design included removal of harvest residues (R), incorporation of residues into the soil by harrowing (I) andmaintenance of residues on the soil surface (S). Understory biomass was sampled in the spring between 2002 and 2006, and every 2 months between March 2006 and March 2007. The latter samples were stratified into biomass, standing dead mass and litter for net above ground primary production (NAPP) assessment. Samples were oven dried, weighed and analysed for nutrient contents. Results showed that understory standing biomass strongly increased from the first to the third year and that quantities of nutrients accumulated in ground vegetation followed similar patterns between the three treatments. Nutrient accumulation in ground vegetation was greater than in tree biomass until at least the second spring after plantation. Bimonthly sampling revealed treatment R to have the largest amounts of standing biomass, standing dead mass, litter and nutrient immobilisation, while treatment S exhibited the lowest values. NAPP (4th–5th year) was 639, 511 and 362 g m 2 year 1, respectively in R, I and S, corresponding the standing biomass increase to 277, 183 and 143 g m 2 year 1. These values are comparable to those observed for litter fall in similar stands (age and tree density) in the same area. The contribution of ground vegetation to nutrient accumulation in the system was unaffected by harvest residue management methods, but further research is necessary in order to establish whether slash management options influence long term tree growth and vegetation dynamics